ChemInform Abstract: Single‐Electron Transmetalation: Synthesis of 1, 1‐Diaryl‐2, 2, 2‐trifluoroethanes by Photoredox/Nickel Dual Catalytic Cross‐Coupling. Issue 21 (6th May 2016) - Ryu, DaWeon; Primer, David N.; Tellis, John C.; Molander, Gary A.
Abstract: To circumvent conventional Suzuki‐coupling protocols, a novel method for the cross‐coupling of benzylic α‐trifluoromethylated alkylboron reagents with (hetero)aryl bromides is developed.